In vitro methane and gas production with inocula from cows and goats fed an identical diet. (15th September 2017) - Mengistu, Genet; Hendriks, Wouter H; Pellikaan, Wilbert F
Abstract: BACKGROUND: Fermentative capacity among ruminants can differ depending on the type of ruminant species and the substrate fermented. The aim was to compare in vitro cow and goat rumen inocula in terms of methane (CH4 ) and gas production (GP), fermentation kinetics and 72 h volatile fatty acids (VFA) production using the browse species Acacia etbaica, Capparis tomentosa, Dichrostachys cinerea, Rhus natalensis, freeze‐dried maize silage and grass silage, and a concentrate as substrates. RESULTS: Total GP, CH4 and VFA were higher ( P  ≤ 0.008) in goat inoculum than cows across substrates. The half‐time for asymptotic GP was lower ( P  < 0.0001) in phase 1 and higher ( P  < 0.012) in phase 2, and the maximum rate of GP was higher ( P  < 0.0001) in phase 1 and phase 3 ( P  < 0.0001) in goats compared to cows. Methane production and as a percentage of total GP was higher ( P  < 0.0001) and the half‐time tended ( P  = 0.059) to be at a later time for goats compared to cows. CONCLUSION: Goat inoculum showed higher fermentative activity with a concomitant higher CH4 production compared to cows. This difference highlights the ability of goats to better utilise browse species and other roughage types. © 2017 Society of Chemical Industry